Carbon Emissions, Human Capital Investment and Economic Development in Nigeria - Afolayan, Olufunmilayo T.; Okodua, Henry; Oaikhenan, Hassan; Matthew, Oluwatoyin (International Journal of Energy Economics and Policy, 2020)
This study examined the joint effect of carbon emissions and health investment on economic development in Nigeria by integrating ecological economics approach with the endogenous growth model. Through the adoption of annual time series spanning 1980-2017, the bounds testing approach of the Autoregressive Distributed Lag (ARDL) framework established the existence of co-integration among the variables in the model. The long run estimates revealed that a 1% increase in government health investments enhances economic development (proxied by GDP per capita) by 0.008% while a 1% increase in the level of CO2 reduces GDP per capita by 0.1%. Furthermore, evidence shows that no causal link exists between fossil fuel consumption (FFC) and CO2 contrary to previous studies. However, unidirectional causality from health outcomes (proxied by life expectancy) to CO2, as well as from CO2 to electricity consumption (ELCON) is observed. Also, increased energy consumption (FFC and ELCON) directly influences GDP per capita. The study recommends that efforts to reduce CO2 should target firms manufacturing cement, asbestos and other dust-generating products as alternative contributors to CO2 accumulation. Equally, mitigating the health effect of CO2 will require effective, efficient and adequate public health investment. Keywords: Carbon Emissions, Government Health Expenditure, Economic Development. JEL Classifications: Q53, H51, O1 DOI: https://doi.org/10.32479/ijeep.8476